Negative active material, secondary battery and electronic device

By adding graphite material, silicon carbon material and hard carbon material to the negative electrode active material of the secondary battery and controlling the proportion of its particles, the performance reduction problem caused by volume changes during the cycle process is solved, and the comprehensive performance improvement of the secondary battery is achieved.

CN119812322APending Publication Date: 2025-04-11NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411997195.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In existing secondary batteries, the volume of silicon-based materials changes greatly during the charge and discharge cycle, resulting in the material powderization and reduced conductivity, thereby reducing the circulation performance, expansion performance and rate performance.

Method used

By adjusting the composition of the negative electrode active material, it includes graphite material, silicon carbon material and hard carbon material, and controlling the proportion of the particle number between (4-20): (1-20) to improve the circulation performance and energy density of the secondary battery.

Benefits of technology

The cycling performance, expansion performance, rate performance and low-temperature performance of the secondary battery are achieved, extending the battery life and improving stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812322A_ABST
    Figure CN119812322A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode active material, a secondary battery and an electronic device, the secondary battery comprises a negative electrode plate and an electrolyte, the negative electrode plate comprises a negative electrode active material, and the negative electrode active material comprises a graphite material, a silicon carbon material and a hard carbon material; wherein the ratio of the particle number of the silicon carbon material to the particle number of the hard carbon material is (4-20): (1-20), and the particle number and the mass content of the graphite material, the silicon carbon material and the hard carbon material in the negative electrode plate are regulated and controlled; the cycle performance, the expansion performance, the low temperature performance and the rate performance of the secondary battery containing the negative electrode active material are comprehensively considered, so that the service life and the stability of the secondary battery are improved, and the secondary battery has high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and in particular relates to a negative electrode active material, a secondary battery and an electronic device. Background Art

[0002] Secondary batteries have the characteristics of high energy density, high operating voltage, and light weight, so they are widely used in electronic products such as mobile phones, laptops, and cameras. As the performance requirements for electronic products increase, the performance requirements for secondary batteries are also gradually increasing.

[0003] Graphite material is the most common negative electrode active material for secondary batteries. In the existing technology, the development of graphite material has reached its theoretical gram capacity of 370mAh / g, and the energy density is difficult to be further improved. Silicon-based materials have a theoretical gram capacity of up to 3600mAh / g and a charge and discharge voltage platform similar to that of graphite, and have broad prospects for application in secondary batteries. However, during the charge and discharge cycle of silicon-based materials, as active ions are embedded and extracted, huge volume changes will occur, causing the silicon-based materials to pulverize and separate from the current collector, thereby causing the negative electrode conductivity to deteriorate, reducing the cycle performance, expansion performance and rate performance of the secondary battery. Summary of the invention

[0004] In view of the above-mentioned problems in the prior art, the first aspect of the present application provides a negative electrode active material, characterized in that the negative electrode active material comprises a graphite material, a silicon-carbon material and a hard carbon material; wherein the ratio of the number of particles of the silicon-carbon material to the number of particles of the hard carbon material is between (4 to 20): (1 to 20); preferably, the ratio of the number of particles of the silicon-carbon material to the number of particles of the hard carbon material is between (4 to 15): (1 to 14).

[0005] In some embodiments of the present application, the graphite material includes at least one of natural graphite or artificial graphite.

[0006] In some embodiments of the present application, there is at least one gap inside the particles of the graphite material, the gap having a width of not less than 10 nm and a length of not less than 100 nm.

[0007] In some embodiments of the present application, the mass content of the graphite material in the negative electrode active material is 45wt% to 94wt%; preferably, the mass content of the graphite material in the negative electrode active material is 50wt% to 90wt%; more preferably, the mass content of the graphite material in the negative electrode active material is 55wt% to 85wt%.

[0008] In some embodiments of the present application, the gram capacity of the graphite material is 300 mAh / g to 370 mAh / g; in some embodiments of the present application, the particle size Dv50 of the graphite material is 5 μm to 20 μm.

[0009] In some embodiments of the present application, the mass content of the silicon-carbon material in the negative electrode active material is 5wt% to 40wt%; preferably, the mass content of the silicon-carbon material in the negative electrode active material is 10wt% to 30wt%.

[0010] In some embodiments of the present application, the silicon content of the silicon-carbon material is 15 wt% to 70 wt%; preferably, the silicon content of the silicon-carbon material is 20 wt% to 65 wt%. In some embodiments of the present application, the particle size Dv50 of the silicon-carbon material is 5 μm to 10 μm.

[0011] In some embodiments of the present application, the mass content of the hard carbon material in the negative electrode active material is 1 wt% to 25 wt%; preferably, the mass content of the hard carbon material in the negative electrode active material is 3 wt% to 10 wt%.

[0012] In some embodiments of the present application, the particle size Dv50 of the hard carbon material is 5 μm to 10 μm.

[0013] In some embodiments of the present application, the negative electrode active material is tested by X-ray diffraction method, and there is a diffraction peak in the range of 2θ of 20° to 30°, and the half-peak width of the diffraction peak is not greater than 2°; the negative electrode active material is tested by Raman test, and there is a diffraction peak in the range of 2θ of 20° to 30°, and the half-peak width of the diffraction peak is not greater than 2°; -1 ±15cm -1 The characteristic peak of silicon-carbon material appears in the region, with a Raman shift of 1338 cm -1 ±15cm -1 The carbon material D peak appears in the region, and the peak intensity of D peak is I d , and at a Raman shift of 1595 cm -1 ±15cm -1 The carbon material G peak appears in the region, and the peak intensity of the G peak is I g , peak intensity ratio I d / I g ≥0.5.

[0014] A second aspect of the present application provides a secondary battery, the secondary battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, the negative electrode sheet comprising the negative electrode active material described in the first aspect of the present application.

[0015] In some embodiments of the present application, the electrolyte includes an additive, and the additive is selected from at least one of the following structural formulas:

[0016]

[0017] In some embodiments of the present application, the mass proportion of the additive in the electrolyte is 0.01% to 10%; preferably, the mass proportion of the additive in the electrolyte is 0.05% to 8%; more preferably, the mass proportion of the additive in the electrolyte is 1% to 5%.

[0018] A third aspect of the present application provides an electronic device, characterized in that the electronic device comprises the secondary battery as described in the second aspect of the present application.

[0019] The present invention improves the cycle performance of a secondary battery containing the negative electrode active material by adjusting the composition and mass content of the negative electrode active material, thereby increasing the life and stability of the secondary battery, and the secondary battery has a high energy density. In addition, the expansion, low temperature and rate performance of the secondary battery are taken into account, so that the secondary battery has better comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a dark field SEM characterization image of the cross section of the negative electrode sheet along the thickness direction in Example 4.

[0021] Figure 2 It is a comparison chart of the cycle capacity retention rate data of Example 9 and Comparative Example 2. DETAILED DESCRIPTION

[0022] The technical solution of the present application is further described below through specific examples and comparative examples, and the specific examples do not limit the protection scope of the present application. Some non-essential modifications and adjustments made by others based on the concept of the present application still fall within the protection scope of the present application.

[0023] For the sake of simplicity, only some numerical ranges are specifically disclosed herein for a certain parameter. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value itself can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.

[0024] In the description herein, unless otherwise specified, “above” and “below” include the number.

[0025] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).

[0026] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0027] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "include" and "comprise" and similar expressions are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0028] In a first aspect, the present application provides a negative electrode active material, the negative electrode active material comprising a graphite material, a silicon-carbon material and a hard carbon material; wherein the ratio of the number of particles of the silicon-carbon material to the number of particles of the hard carbon material is between (4-20): (1-20), and the ratio is between 0.5-20; preferably, the ratio of the number of particles of the silicon-carbon material to the number of particles of the hard carbon material is between (4-15): (1-14), and the ratio is between 0.5-15. Specifically, the ratio of the number of particles of the silicon-carbon material to the number of particles of the hard carbon material can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 2.0, 3.0, 4.0, 5.0, 10.0, 15.0, 20.0 or a range consisting of any two of the above values. When the ratio of the number of silicon-carbon material particles to the number of hard carbon material particles is within the above range, it can take into account both high gram capacity, so that the secondary battery has a high energy density and good battery performance such as cycle performance, while taking into account the expansion, low temperature and rate performance of the secondary battery, so that the secondary battery has better overall performance.

[0029] In some embodiments of the present application, the graphite material includes at least one of natural graphite or artificial graphite.

[0030] In some embodiments of the present application, there is at least one gap with a width of not less than 10 nm and a length of not less than 100 nm inside the particles of the graphite material, wherein the length is the farthest distance between two points on the edge of the gap, and the width is the distance between the line segments perpendicular to the length and where the two points are located on the edge of the gap; the expansion performance and cycle performance of the secondary battery can be further improved.

[0031] In some embodiments of the present application, the mass content of the graphite material in the negative electrode active material is 45wt% to 94wt%; preferably, the mass content of the graphite material in the negative electrode active material is 50wt% to 90wt%; more preferably, the mass content of the graphite material in the negative electrode active material is 55wt% to 85wt%. Specifically, the mass percentage of the graphite material in the negative electrode active material can be 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 94wt% or a range consisting of any two of the above values. When the mass content of the graphite material is within the above range, it is beneficial to improve the cycle performance and rate performance of the secondary battery.

[0032] In some embodiments of the present application, the gram capacity of the graphite material is 300 mAh / g to 370 mAh / g; in some embodiments of the present application, the particle size Dv50 of the graphite material is 5 μm to 20 μm.

[0033] In some embodiments of the present application, the silicon content in the silicon-carbon material is 15wt% to 70wt%; preferably, the silicon content in the silicon-carbon material is 20wt% to 65wt%. Specifically, the silicon content in the silicon-carbon material can be 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt% or a range consisting of any two of the above values. When the silicon content in the silicon-carbon material is within the above range, it is beneficial to balance the gram capacity and volume expansion of the silicon-carbon material, thereby improving the overall performance of the secondary battery.

[0034] In some embodiments of the present application, the mass content of the silicon-carbon material in the negative electrode active material is 5wt% to 40wt%; preferably, the mass content of the silicon-carbon material in the negative electrode active material is 10wt% to 30wt%. Specifically, the mass percentage of the silicon-carbon material in the negative electrode active material can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or a range consisting of any two of the above values. When the mass percentage of the silicon-carbon material in the negative electrode active material is within the above range, it helps to balance the gram capacity and volume expansion of the secondary battery and the rate performance, and improve the comprehensive performance of the secondary battery.

[0035] In some embodiments of the present application, the particle size Dv50 of the silicon-carbon material is 5 μm to 10 μm.

[0036] In some embodiments of the present application, the mass content of the hard carbon material in the negative electrode active material is 1wt% to 25wt%; preferably, the mass content of the hard carbon material in the negative electrode active material is 3wt% to 10wt%. Specifically, the mass percentage of the hard carbon material in the negative electrode active material can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or a range consisting of any two of the above values. When the mass content of the hard carbon material in the negative electrode active material is within the above range, it can effectively slow down the cycle performance and expansion performance of the secondary battery containing silicon-carbon material, and can also reduce the impact on the energy density of the secondary battery.

[0037] In some embodiments of the present application, the particle size Dv50 of the hard carbon material is 5 μm to 10 μm.

[0038] In some embodiments of the present application, the hard carbon material can be purchased directly from the market or synthesized independently from a hard carbon precursor. In some embodiments of the present application, the hard carbon precursor can be at least one of a resin polymer, a coal-based raw material, asphalt, and a biomass material; in some embodiments of the present application, the polymer can include at least one of an epoxy resin, a phenolic resin, polyfurfuryl alcohol, polyvinyl alcohol, and polythiophene; the biomass material can include at least one of a fruit shell, lignin, sodium lignin sulfonate, glucose, starch, and the like.

[0039] In some embodiments of the present application, the negative electrode active material is tested by X-ray diffraction method, and there is a diffraction peak in the range of 2θ of 20° to 30°, and the half-peak width of the diffraction peak is not greater than 2°; the negative electrode active material is tested by Raman method, and there is a diffraction peak in the range of 2θ of 20° to 30°, and the half-peak width of the diffraction peak is not greater than 2°; -1 ±15cm -1The characteristic peak of silicon-carbon material appears in the region, with a Raman shift of 1338 cm -1 ±15cm -1 The carbon material D peak appears in the region, and the peak intensity of D peak is I d , and at a Raman shift of 1595 cm -1 ±15cm -1 The carbon material G peak appears in the region, and the peak intensity of the G peak is I g , peak intensity ratio I d / I g ≥0.5.

[0040] A second aspect of the present application provides a secondary battery, which comprises a positive electrode plate, an electrolyte, a separator and a negative electrode plate, wherein the negative electrode plate comprises the negative electrode active material as described in the first aspect of the present application.

[0041] The negative electrode plate described in the present application also includes a binder, a thickener and a negative electrode current collector. In some embodiments of the present application, the binder includes but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.

[0042] In some embodiments of the present application, the thickener includes but is not limited to at least one of carboxymethyl cellulose (sodium), hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid (ester), oxidized starch, phosphorus-oxidized starch, casein, etc.

[0043] In some embodiments of the present application, the current collector includes but is not limited to at least one of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a polymer substrate coated with a conductive metal.

[0044] In some embodiments of the present application, the negative electrode plate further includes a conductive agent, which includes but is not limited to carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof; in some embodiments, the carbon-based material is selected from carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof; in some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.

[0045] In some embodiments of the present application, the electrolyte includes an additive, and the additive is selected from at least one of the following structural formulas:

[0046]

[0047] In some embodiments of the present application, the mass proportion of the additive in the electrolyte is 0.01% to 10%; preferably, the mass proportion of the additive in the electrolyte is 0.05% to 8%; more preferably, the mass proportion of the additive in the electrolyte is 1% to 5%. The additive can form a low-impedance flexible interface film on the surface of the negative electrode and / or the positive electrode, thereby protecting the negative electrode and / or the positive electrode, thereby improving the cycle performance and expansion performance of the secondary battery.

[0048] In some embodiments of the present application, the positive electrode sheet includes a current collector and a positive electrode active material, a binder, and a conductive carbon additive located on the surface of the current collector. The present application has no particular restrictions on the positive electrode current collector, the positive electrode active material, the conductive agent, and the binder, as long as they can achieve the purpose of the present application.

[0049] In some embodiments of the present application, the positive electrode material includes but is not limited to lithium cobalt oxide (LiCoO 2 ), lithium iron phosphate (LiFePO 4 ), ternary cathode materials (NCM333, NCM523, NCM622, NCM811, NCA, etc.), lithium manganese oxide (LiMn 2 O 4 ), lithium-rich manganese-based cathode (xLi 2 MnO 3 ·(1-x)LiMO 2 ), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 ) and the like; in some embodiments of the present application, the positive electrode current collector may include aluminum; in some embodiments of the present application, the binder may include but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.; in some embodiments of the present application, the conductive material may include but is not limited to: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof; in some embodiments of the present application, the carbon-based material is selected from carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof; in some embodiments of the present application, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments of the present application, the conductive polymer is a polyphenylene derivative.

[0050] The present application has no particular restrictions on the isolation membrane, as long as it can achieve the purpose of the present application. In some embodiments of the present application, the isolation membrane may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.

[0051] A third aspect of the present application provides an electronic device, characterized in that the electronic device comprises the secondary battery as described in the second aspect of the present application.

[0052] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a drone, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, or a large household battery.

[0053] The present application is described in more detail below through specific embodiments.

[0054] Example 1

[0055] Preparation of negative electrode active materials

[0056] (1) Preparation of graphite material: The graphite used in this embodiment is natural graphite with a gram capacity of 360 mAh / g and a particle size Dv50 of 14 μm.

[0057] (2) Preparation of silicon-carbon material: Linear phenolic resin (RF) and hexamethylenetetramine (HMT) were mixed in a weight ratio of 93:7 to form a mixture. The mixing method was ball milling, and the ball milling speed was 400 r / min and the ball milling time was 10 h. The ball-milled mixture was heated to 130°C and kept warm for 10 h for curing. The cured mixture was transferred to a box furnace and heated to 850°C for carbonization for 2 h in a nitrogen atmosphere, and then cooled and transferred to a rotary kiln for activation in a carbon dioxide atmosphere for 9 h to obtain a porous carbon skeleton. After crushing and grading (Dv50 is 8μm), the porous carbon skeleton continues to be heated to 300°C at a rate of 2°C / min in a tubular furnace under an argon atmosphere, and then the atmosphere is switched to a silane mixture (30% silane and 70% argon by mass) and continued to be heated to 480°C. After deposition at 480°C for 12 hours, the atmosphere is switched to an acetylene mixture (20% acetylene and 80% argon by mass) and continued to be deposited at 500°C for 10 hours, then switched to nitrogen, and then cooled to room temperature 25°C to obtain a silicon-carbon material.

[0058] (3) Preparation of hard carbon materials: Commercial coconut shells were used as raw materials. The specific preparation process was as follows: 100 g of coconut shells were weighed, crushed into particles less than 1 mm, and then soaked in 1 M sodium hydroxide solution for 10 h, filtered and dried; then, in a nitrogen atmosphere, the dried alkali-treated coconut shells were heated to 800 °C at a heating rate of 5 °C / min in a tube furnace, kept warm for 2 h, and then cooled naturally; the obtained black powder was washed twice with water, then washed twice with acid, and then washed twice with water, dried, and graded by air flow crushing (Dv50 was 5 μm), then the sample was heated to 1100 °C at a heating rate of 5 °C / min, kept warm for 2 h, and then cooled to 880 °C. The atmosphere was switched to CH 4 After 5 h of heat preservation, the atmosphere was switched to N 2 , and then began to cool down naturally to obtain hard carbon material.

[0059] (4) The three materials prepared in the above (1)-(3) were mixed uniformly according to the mass contents of 89wt%, 10wt% and 1wt% respectively to obtain a negative electrode active material.

[0060] Preparation of negative electrode

[0061] The negative electrode active material, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in a proper amount of solvent deionized water at a mass ratio of 97:2:1 to form a negative electrode slurry with a solid content of 40%; the negative electrode slurry was coated on a negative electrode collector copper foil with a thickness of 6 μm, dried at 85°C, cold pressed, cut, slit, and vacuum dried at 120°C for 12 hours to obtain a negative electrode sheet.

[0062] Preparation of secondary batteries

[0063] (1) Preparation of positive electrode sheet: The positive electrode active material (lithium cobalt oxide is used as an example in all embodiments of this application), the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred thoroughly to obtain a positive electrode slurry with a solid content of 72wt% and a uniform system. The positive electrode slurry is evenly coated on a positive electrode current collector aluminum foil with a thickness of 6μm, dried at 85°C, and then cold pressed, cut and slit, and dried at 85°C under vacuum for 4h to obtain a positive electrode sheet.

[0064] (2) Preparation of electrolyte: In dry (H 2 In an argon atmosphere glove box (0<1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed evenly at a mass ratio of EC:EMC:DEC=30:50:20, 1,3-propane sultone and fluoroethylene carbonate were added, and then the additive structural formula 2 was added, dissolved and stirred thoroughly, and then lithium salt LiPF was added. 6 , and then mixed evenly to obtain an electrolyte; based on the mass of the electrolyte, LiPF 6 The mass proportion of is 12.5%, the mass proportion of 1,3-propane sultone is 1.5%, the mass proportion of fluoroethylene carbonate is 2%, and the mass proportion of the additive structure 2 is 1%.

[0065] (3) Preparation of isolation membrane: A 7 μm thick polyethylene (PE) porous polymer film was used as the isolation membrane.

[0066] (4) Secondary battery assembly: The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrodes to play an isolating role. The sheets are then wound, the tabs are welded, and the sheets are placed in an outer packaging foil aluminum-plastic film. The electrolyte is injected and the sheets are vacuum packaged, left to stand, formed, shaped, and tested for capacity to obtain a soft-pack secondary battery.

[0067] Example 2 to Example 15, Comparative Example 1 to Comparative Example 3

[0068] The processes of Examples 2 to 15 and Comparative Examples 1 to 3 are the same as those of Example 1, except for the mass contents of graphite material, silicon-carbon material and hard carbon material, the type of hard carbon material, and the silicon content of silicon-carbon material when preparing the negative electrode active material, as shown in Table 1.

[0069] Example 16 to Example 18, Comparative Example 4

[0070] The experimental parameters and processes of Examples 16 to 18 and Comparative Example 4 are the same as those of Example 2, except that the types and mass proportions of additives are different during the preparation of the electrolyte, as shown in Table 4.

[0071] Test Method

[0072] The negative electrode active materials and secondary batteries in the above examples and comparative examples were subjected to the following tests, respectively. The test results are shown in Table 2, Table 3 and Table 4.

[0073] (1) Scanning electron microscope characterization: The secondary battery was discharged to 3.0V at 1C, and then charged to 50% of the rated capacity, and then disassembled in a glove box to obtain the negative electrode sheet, which was transferred to a drying room with a humidity of <2%. The cross section of the negative electrode sheet along the thickness direction was obtained by ion polishing, and then quickly transferred to a scanning electron microscope to characterize the obtained cross section. First, a 15μm×20μm range of the cross section was selected for dark field SEM characterization, and the internal morphology of the material particles was carefully recorded. The particles with no less than one gap inside the particles and no less than 10nm×100nm were marked as graphite materials (first particles), and their number was recorded; then, the backscatter photography mode was turned on, and in the same SEM area, the particles with higher brightness than the graphite material under the backscatter condition and no gap inside the particles were marked as silicon-carbon materials (second particles), and their number of particles was recorded; finally, the particles other than the graphite material and the silicon-carbon material were marked as hard carbon materials (third particles), and their number of particles was recorded. Repeat the above operation in a range of 15μm×20μm, and summarize the number of particles of graphite material, silicon-carbon material and hard carbon material. After performing the above operation in 50 regions, calculate the average number of particles of graphite material, silicon-carbon material and hard carbon material as the number of particles of graphite material, the number of particles of silicon-carbon material and the number of particles of hard carbon material; Figure 1 As shown, graphite material (first particles), silicon carbon material (second particles) and hard carbon material (third particles) exist in the cross section of the negative electrode sheet along the thickness direction.

[0074] Then, EDS element analysis was performed on the silicon-carbon material to obtain the element distribution mapping and spectrum of elements such as C and Si, and the mass content of each element was obtained, and the mass content of silicon was recorded.

[0075] (2) Raman test: A spectrometer (JobinYvon LabRAM HR) was used to test the cross-section of the negative electrode sheets of each embodiment and comparative example along the thickness direction. The light source was 532 nm and the test range was 50 cm. -1 Up to 2000cm -1 After the test is completed, pay attention to 450cm -1 Up to 550cm -1Range and 1000~2000cm -1 For characteristic peaks within the range, the maximum point of the peak is taken as the peak position of the peak, and 1 / 2 of the difference of the horizontal coordinates at half the peak is taken as the half-peak width of the peak. -1 ±15cm -1 and 1595cm -1 ±15cm -1 The peaks within the range are marked as D peak and G peak, respectively, and their intensities are identified after deducting the baseline to obtain the value of their intensity ratio Id / Ig.

[0076] (3) X-ray diffraction (XRD) test: The negative electrode active material was tested using an X-ray powder diffractometer (XRD, instrument model: Bruker D8 ADVANCE) with a test range of 10° to 90° and a scanning speed of 5° / min. After the test, the characteristic peak in the range of 20° to 30° was focused on, the maximum point of the peak was taken as the peak position, and 1 / 2 of the difference in the horizontal coordinate at half the peak was taken as the half-peak width of the peak.

[0077] (4) Button test: Punch the above negative electrode sheet into a 14mm diameter original sheet, weigh it (weigh the corresponding empty copper foil area to obtain the weight of the substrate) and calculate the weight of the negative electrode active material before starting to assemble the button battery. The button battery is assembled with the obtained negative electrode sheet as the working electrode and the lithium sheet as the counter electrode. The two are aligned up and down and separated by an isolation membrane and the electrolyte is added to form a button battery. After the button battery is assembled, let it stand for 8 hours before starting the test. First, discharge it at a constant current density of 25mA / g to 0V vs Li + / Li, then discharge at 0V constant voltage to a current density of 2.5mA / g, and record the gram capacity of this step; then charge at a current density of 25mA / g to 2.0Vvs Li + / Li, for the obtained charge capacity, the gram capacity at 0-0.3V is taken as A / mAh / g, the gram capacity at 0-0.8V is taken as B / mAh / g, and the gram capacity at 0-2.0V is taken as C / mAh / g.

[0078] (5) Cyclic performance test and expansion test of secondary batteries: The secondary batteries in each embodiment and comparative example were left at rest for 5 minutes at a test temperature of 25°C, then charged at a constant current of 1C to a voltage of 4.5V, and then charged at a constant voltage to 0.05C; discharged at a constant current of 1C to a voltage of 3V, which was recorded as one cycle, and the capacity at this time was recorded as D0. This cycle was repeated for 600 times, and the last discharge capacity was recorded as D1; ​​after 600 cycles at 25°C, the cycle capacity retention rate was D1 / D0, in units of %. Five samples were tested for each embodiment or comparative example, and the average value was taken. In the above-mentioned cycle process, after the first cycle, the secondary battery was discharged to 50% SOC, and the thickness of the diagonal center of the secondary battery was tested, which was recorded as h0. After each 100 cycles, the thickness of the secondary battery was recorded at the same position at 50% SOC using the same test method. After 800 cycles, the thickness of the secondary battery obtained was h8, and at this time, the expansion rate of the secondary battery was (h8-h0) / h0×100%.

[0079] (6) Secondary battery volume energy density test: At room temperature, charge the battery to 4.5V at 1C, then charge it to 0.05C at 4.5V constant voltage; let it stand for 5 minutes, then discharge it to 3.0V at 0.025C constant current, let it stand for 5 minutes, record the capacity at this time as D, in mAh, then charge the secondary battery to 4.0V at 1.0C, measure the length, width and thickness of the secondary battery at this time, and calculate the volume V of the secondary battery, in mm 3 , volume energy density calculation: VED = (D × 3.9 × 1000) / V, unit is Wh / L. Five samples were tested for each embodiment or comparative example, and the average value was taken.

[0080] (7) Test of rate and low temperature performance of secondary battery: The secondary battery in each embodiment and comparative example was left at rest for 5 minutes at a test temperature of 25°C, then charged at a constant current of 0.2C to a voltage of 4.5V, and then charged at a constant voltage to 0.05C; discharged at a constant current of 0.2C to a voltage of 3V, and the capacity at this time was recorded as D2; then charged at a constant current of 2C to a voltage of 4.5V, and then charged at a constant voltage to 0.05C; discharged at a constant current of 2C to a voltage of 3V, and the capacity at this time was recorded as D3, and the size of D3 / D2×100% was used as an indicator to measure the rate performance. Then, at a test temperature of 25°C, charged at a constant current of 0.2C to a voltage of 4.5V, and then charged at a constant voltage to 0.05C; the secondary battery was transferred to a -20°C environment, left for 5 hours, and then discharged at a constant current of 0.2C to a voltage of 3V, and the capacity at this time was recorded as D4, and the size of D4 / D2×100% was used as an indicator to measure the low temperature performance.

[0081] Table 1 Preparation parameters of negative electrode active materials

[0082]

[0083]

[0084] Table 2 Characteristic parameters of negative electrode active materials

[0085]

[0086] Table 3 Performance parameters of negative electrode active materials and secondary batteries

[0087]

[0088] Table 4 Additive types and proportions and performance test results

[0089]

[0090] Note: “ / ” in Tables 1 to 4 indicates that there is no corresponding substance or parameter.

[0091] It can be seen from Examples 1 to 6 and Comparative Example 3 that the negative electrode active material comprising graphite material, silicon-carbon material and hard carbon material can improve the cycle performance, expansion performance and rate performance of the secondary battery compared with the negative electrode active material comprising only graphite material or comprising graphite material and silicon-carbon material; According to Examples 1 to 4 and Examples 7 to 10, it can be seen that by adjusting the mass content of carbon-silicon material and hard carbon material, when the mass content of silicon-carbon material increases, the energy density and gram capacity are significantly increased, and the adjustment of the mass content of hard carbon material can effectively improve the influence on other properties of the secondary battery caused by the addition of silicon-carbon material; Therefore, the comprehensive performance of the secondary battery is improved by adjusting the type of hard carbon material, the mass content of added hard carbon material and the ratio of the number of particles between silicon-carbon material and hard carbon material.

[0092] According to Example 2, Comparative Example 4 and Examples 16 to 18, it can be seen that adding additives to the electrolyte can further improve the capacity retention rate of the secondary battery and reduce its expansion rate.

[0093] It can be seen from the embodiments of the present application and the comparative examples that the negative electrode active material contains graphite material, silicon-carbon material and hard carbon material. By adjusting the ratio of the number of silicon-carbon material particles to the number of hard carbon material particles to be between (4 to 20): (1 to 20), a secondary battery with higher gram capacity and energy density and better overall performance can be obtained.

[0094] The negative electrode active material and the secondary battery of the present application are introduced in detail above. Specific examples are used in this article to illustrate the scheme of the present application, but the specific examples are only used to help understand the main purpose and core of the present application and do not constitute a limitation on the scope of protection.

Claims

1. A negative electrode active material, characterized in that: The negative electrode active material comprises a graphite material, a silicon-carbon material and a hard carbon material; wherein the ratio of the number of particles of the silicon-carbon material to the number of particles of the hard carbon material is between (4-20): (1-20); Preferably, the ratio of the number of particles of the silicon-carbon material to the number of particles of the hard carbon material is between (4-15):(1-14).

2. The negative electrode active material according to claim 1, characterized in that The silicon content in the silicon-carbon material is 15wt% to 70wt%; Preferably, the silicon content in the silicon-carbon material is 20wt% to 65wt%.

3. The negative electrode active material according to claim 1, characterized in that The graphite material comprises at least one of natural graphite or artificial graphite, and the mass content of the graphite material in the negative electrode active material is 45wt% to 94wt%; Preferably, the mass content of the graphite material in the negative electrode active material is 50wt% to 90wt%; More preferably, the mass content of the graphite material in the negative electrode active material is 55wt% to 85wt%.

4. The negative electrode active material according to claim 1, characterized in that The mass content of the silicon-carbon material in the negative electrode active material is 5wt% to 40wt%; Preferably, the mass content of the silicon-carbon material in the negative electrode active material is 10 wt % to 30 wt %.

5. The negative electrode active material according to claim 1, characterized in that The mass content of the hard carbon material in the negative electrode active material is 1wt% to 25wt%; Preferably, the mass content of the hard carbon material in the negative electrode active material is 3wt% to 10wt%.

6. The negative electrode active material according to any one of claims 1 to 5, characterized in that: It meets at least one of the following characteristics: (1) The negative electrode active material is tested by X-ray diffraction method, and there is a diffraction peak in the range of 2θ of 20° to 30°, and the half-peak width of the diffraction peak does not exceed 2°; (2) The negative electrode active material is tested by Raman and has a characteristic peak at the following Raman shift: 480 cm -1 ±15cm -1 , 1338cm -1 ±15cm -1 , 1595cm -1 ±15cm -1 ; Among them, 1338cm -1 ±15cm -1 A D peak appears at , and the peak intensity of the D peak is 1 d , 1595cm -1 ±15cm -1 A G peak appears at 1 g , I d / I g ≥0.

5.

7. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, and the negative electrode sheet comprises the negative electrode active material according to any one of claims 1 to 6.

8. The secondary battery according to claim 7, characterized in that The electrolyte contains an additive, and the additive is selected from at least one of the following structural formulas:

9. The secondary battery according to claim 8, characterized in that The mass proportion of the additive in the electrolyte is 0.01% to 10%; Preferably, the mass proportion of the additive in the electrolyte is 0.05% to 8%; More preferably, the additive accounts for 1% to 5% by mass in the electrolyte.

10. An electronic device, characterized in that: The electronic device comprises the secondary battery as claimed in any one of claims 7 to 9.